Synergistic band convergence and defect engineering boost thermoelectric performance of SnTe. (30th September 2021) - Dong, Ximeng; Cui, Wenlin; Liu, Wei-Di; Zheng, Shuqi; Gao, Lei; Yue, Luo; Wu, Yue; Wang, Boyi; Zhang, Zipei; Chen, Liqiang; Chen, Zhi-Gang
Highlights: AgCl-doping and Sb-alloying enhance thermoelectric performance of SnTe stepwise. AgCl-doping simultaneously enlarges band gap and achieves band convergence of SnTe. Dense point defects effectively reduce lattice thermal conductivity of SnTe. Sb-alloying effectively optimizes carrier concentration of SnTe. Abstract: As an eco-friendly thermoelectric material, SnTe has attracted extensive attention. In this study, we use a stepwise strategy to enhance the thermoelectric performance of SnTe. Firstly, AgCl is doped into SnTe to realize band convergence and enlarge the band gap of AgCl-doped SnTe. AgCl-doping also induces dense point defects, strengthens the phonon scattering, and reduces the lattice thermal conductivity. Secondly, Sb is alloyed into AgCl-doped SnTe to further optimize the carrier concentration and simultaneously reduce the lattice thermal conductivity, leading to improved thermoelectric dimensionless figure of merit, ZT . Finally, (Sn0.81 Sb0.19 Te)0.93 (AgCl)0.07 has approached the ZT value as high as ∼0.87 at 773 K, which is 272 % higher than that of pristine SnTe. This study indicates that stepwise AgCl-doping and Sb-alloying can significantly improve thermoelectric performance of SnTe due to synergistic band engineering, carrier concentration optimization and defect engineering.